Eculizumab Therapy Leads to Rapid Resolution of Thrombocytopenia in Atypical Hemolytic Uremic Syndrome - Han-Mou Tsai; Elizabeth Kuo (Advances in Hematology)
Eculizumab is highly effective in controlling complement activation in patients with the atypical hemolytic uremic syndrome (aHUS). However, the course of responses to the treatment is not well understood. We reviewed the responses to eculizumab therapy for aHUS. The results show that, in patients with aHUS, eculizumab therapy, when not accompanied with concurrent plasma exchange therapy, led to steady increase in the platelet count and improvement in extra-renal complications within 3 days. By day 7, the platelet count was normal in 15 of 17 cases. The resolution of hemolytic anemia and improvement in renal function were less predictable and were not apparent for weeks to months in two patients. The swift response in the platelet counts was only observed in one of five cases who received concurrent plasma exchange therapy and was not observed in a case of TMA due to gemcitabine/carboplatin. In summary, eculizumab leads to rapid increase in the platelet counts and resolution of extrarenal symptoms in patients with aHUS. Concurrent plasma exchange greatly impedes the response of aHUS to eculizumab therapy. Eculizumab is ineffective for gemcitabine/carboplatin associated TMA.